2002
DOI: 10.1111/j.1365-2508.2002.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Delivering an effective outpatient service in gynaecology: an assessment of patient preference

Abstract: Objective  To examine the cost implications of outpatient versus daycase hysteroscopy to the National Health Service, the patient and their employer. Design and interventions  Randomised controlled trial. Setting  The gynaecology clinic of a large teaching hospital. Participants  Ninety‐seven women with abnormal uterine bleeding requiring investigation. Methods  Women were randomly allocated to either outpatient or daycase hysteroscopy. They were asked to complete diaries recording expenses and time off work. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…Nowadays, diagnostic hysteroscopy is performed according to the so‐called vaginoscopic approach without use of speculum or tenaculum, reducing discomfort significantly 101 . Furthermore, as a result of recent advances in endoscopic instrumentation there is evidence suggesting that outpatient therapeutic hysteroscopic procedures provide significant cost savings and are preferred by women compared to day case procedures 102,103 . Whether these improvements make diagnostic hysteroscopy comparable to saline infusion sonography regarding cost‐effectiveness and patient compliance remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, diagnostic hysteroscopy is performed according to the so‐called vaginoscopic approach without use of speculum or tenaculum, reducing discomfort significantly 101 . Furthermore, as a result of recent advances in endoscopic instrumentation there is evidence suggesting that outpatient therapeutic hysteroscopic procedures provide significant cost savings and are preferred by women compared to day case procedures 102,103 . Whether these improvements make diagnostic hysteroscopy comparable to saline infusion sonography regarding cost‐effectiveness and patient compliance remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These include the avoidance of general anaesthesia and its associated risks, faster return to normal activities and less time away from home and work 7 . Furthermore, there is evidence to suggest that outpatient gynaecological procedures provide significant cost savings and are preferred by women when compared with daycase procedures 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…The reasons for the under‐utilisation of this service might include a perceived lack of women who would want the service, expensive capital outlay to purchase the equipment and a lack of expertise within the unit. However, a survey of women's preferences show they would favour an outpatient hysteroscopy if given a choice between that and daycase hysteroscopy 8 . This study has shown that although there is a higher capital equipment cost when setting up the outpatient hysteroscopy service, an overall cost saving is soon seen when compared with daycase hysteroscopy.…”
Section: Discussionmentioning
confidence: 84%